Biodegradation of phenol in treated water from the oil industry to re-use in agricultural crops - Pardo-Díaz, Sergio (2017)
Oil exploitation and the usage of its derivatives have undeniably contributed to the technological advance worldwide. This industrial activity, however, generates several by-products that can threaten environmental sustainability. Seawage, for example, can contain organic pollutants and heavy metals; therefore, its deposition must be preceded by adequate water treatment. In this study, we isolated, characterized, and molecularly identified eight bacteria on the basis of their capability to degrade phenol. First, we determined the rates of bacterial growth and phenol degradation using different concentrations of the aromatic hydrocarbon (500, 800 and 1 200 mg / L), and then used sequential statistical designs to select optimal conditions for its degradation. Results showed that all isolated strains were capable of degrading phenol as the sole carbon source; the degradation kinetics and phenol tolerance, however, widely varied among strains. We chose the strain Pseudomonas sp. Sps1 for further studies due to its remarkable tolerance and capability to degrade phenol. By using a Plackett Burman design, followed by a fractionated factorial design in which several carbon, nitrogen, and phosphorus sources were evaluated, and phenol degradation was used as the response variable, we found optimal conditions for phenol degradation by Sps1. Finally, we compared phenol degradation in seawage by the use or not of the optimal conditions established by the statistical methods. Results showed that biostimulation dramatically increased phenol degradation compared with the control. In conclusion, we found that bioaugmentation with the native bacteria Sps1 and a statistically-based biostimulation approach provided an economically and environmentally friendly alternative for the removal of pollutants from oil industry sewage.